Prophylactic antibiotics in elective hip and knee arthroplasty: an analysis of organisms reported to cause infections and national survey of clinical practice - Hickson, C; Metcalfe, D; Elgohari, S; Oswald, T; Masters, J; Rymaszewska, M; Reed, M; Sprowson, A (British Editorial Society of Bone and Joint Surgery, 2015)
We wanted to investigate regional variations in the organisms reported to be causing peri-prosthetic infections and to report on prophylaxis regimens currently in use across England.Analysis of data routinely collected by Public Health England's (PHE) national surgical site infection database on elective primary hip and knee arthroplasty procedures between April 2010 and March 2013 to investigate regional variations in causative organisms. A separate national survey of 145 hospital Trusts (groups of hospitals under local management) in England routinely performing primary hip and/or knee arthroplasty was carried out by standard email questionnaire.Analysis of 189 858 elective primary hip and knee arthroplasty procedures and 1116 surgical site infections found statistically significant variations for some causative organism between regions. There was a 100% response rate to the prophylaxis questionnaire that showed substantial variation between individual trust guidelines. A number of regimens currently in use are inconsistent with the best available evidence.The approach towards antibiotic prophylaxis in elective arthroplasty nationwide reveals substantial variation without clear justification. Only seven causative organisms are responsible for 89% of infections affecting primary hip and knee arthroplasty, which cannot justify such widespread variation between prophylactic antibiotic policies. Cite this article: Bone Joint Res 2015;4:181-189.